Hubungan Perilaku Merokok Anggota Keluarga dengan Kejadian Bronkopneumonia pada Balita di RSU Gmim Pancaran Kasih Manado - Israel Simbar; Petronela Mamentu; Sri Wahyuni (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
The smoking habits of family members are one the causes of Bronchopenumonia in toddlers since smoking can damage the air quality around toddlers. The purpose of this research was to find out the correlation between family members' smoking behavior with the incidence of bronchopneumonia in toddlers at the GMIM Pancaran Kasih General Hospital Manado. This study used an analytic descriptive method with a cross-sectional approach. It was conducted at the GMIM Pancaran Kasih General Hospital Manado from January to February 2025. The sample of this study amounted to 30 respondents. Data collection used a family member smoking behavior questionnaire and Bronchopneumonia data observation sheet. The results showed that there are 22 toddlers had severe bronchopneumonia with severe smoking of their family members, and 8 toddlers had mild bronchopneumonia with mild smoking behavior of their family members. The Chi-Square test showed p=0.007, with a p value smaller than alpha (α) = 0.05. The conclusion in this study is that there is a highly significant correlation between family members' smoking behavior and the incidence of bronchopneumonia in toddlers at the GMIM Pancaran Kasih General Hospital Manado. Suggestions for families should be able to stop smoking behavior that will have an impact on toddlers and surrounding people.